YOUTUBE AS A MEDIUM FOR INDONESIAN TODDLERS’ SECOND LANGUAGE ACQUISITION (AN ANALYSIS THROUGH CHILDREN SONGS) - Farahsani, Yashinta; Rini, Ika Puspita; Jaya, Patria Handung (Faculty of Humanities, Diponegoro University, 2020)
Language acquisition for children is started when they produce words on their own. Children’s language normally develop in line with their age. Usually they can produce sentence and speak their mother tongue language fluently at the age of three. In the same time, children are able to acquire other language which is called second language acquisition (SLA). In Indonesia, English has become second language that has become the main subject at school, from the elementary level to the university level. Toddlers are children at the range of age between 2-3 years. This is the peak time to acquire language, and at this age, children are able to create phrase or simple sentence. Since the technology has developed very rapidly, children also can get more facilities to learn language. One of the media to learn language is YouTube. Using interview method, the writers did interview to 21 respondents as the parents of pre-school students. There were four questions to answer and the answers were described based on the respondents’ opinion. The research results that children can start to learn English through YouTube by watching English songs. Their attraction in watching is followed by imitating the word, the way the characters sing, and also the manner. Parents become guide to improve the children’s process of English learning after they watched YouTube.